Empowering fisherwomen leaders helped reduce the effects of the COVID-19 pandemic on fishing communities: Insights from Brazil. (January 2022) - Silva, Monalisa R.O.; Silva, André B.; Barbosa, Jaciana C.; Amaral, Cássia; Lopes, Priscila F.M.
Abstract: Small-scale fishers in the developing world have been particularly affected by the COVID-19 pandemic given that they belong to one of the most socioeconomically vulnerable groups. In Brazil, one of the countries most affected by the pandemic, it was expected early on that the economy and wellbeing of fishers would be negatively impacted, yet fishers were expected to show some adaptive and coping mechanisms. To assess whether this was the case, 40 fishers, who are also leaders of fishing associations representing over 80 thousand fishers throughout the country, were interviewed. Results revealed that female leaders appraised the economic and health / wellbeing impacts to be harsher on fishers than men did. Moreover, fishers on the coast were found to be better able to adapt than those inland, although both had low levels of adaptive capacity. The nature of coping and adaptive mechanisms was also found to be different between locations. Whereas leaders from coastal associations stated that most of the adaptive responses occurred in the post-harvest sector (e.g., changes to the types of sales and changes to supply chain actors), leaders from inland communities stated that the changes that occurred related specifically to fishing (e.g., decrease in effort and changes in fishing grounds). These findings suggest that: 1) women may be better prepared to respond to COVID-19 because their appraisal may be more realistic than men, 2) the historic vulnerability of fishing communities may limit their adaptative capacity, and 3) coastal fishers have likely found ways to maintain part of their trade, contrary to inland fishers. Thus, to better help small-scale fisheries to cope with this particular pandemic or other large disruptive impacts, it would be recommended to invest in women in leadership roles while also guaranteeing that fishers have the minimal conditions to cope with and adapt to impacts. The latter can be done by assuring emergency cash transfers for the duration of the impact, as with the still ongoing pandemic, and investing in building fisher resilience for future shocks. Highlights: COVID-19 has had a significant impact on Brazilian fishing communities. Fisher responses and adaptative strategies provide useful insights for policy measures. Money transfer programs are key to helping fishers in both coastal and inland areas. Fisherwomen leaders perceive the impacts of COVID-19 to be more severe than their male counterparts do. Investing in women in leadership roles is likely to promote faster and better responses to impacts.